Hierarchical 2D yarn-ball like metal–organic framework NiFe(dobpdc) as bifunctional electrocatalyst for efficient overall electrocatalytic water splitting. Issue 43 (2nd November 2020) - Qi, Lixia; Su, Ya-Qiong; Xu, Zichen; Zhang, Guanghui; Liu, Kang; Liu, Min; Hensen, Emiel J. M.; Lin, Ryan Yeh-Yung
Abstract : MOF electrocatalyst, NiFe(dobpdc) (dobpdc = 4, 4′-dioxidobiphenyl-3, 3′-dicarboxylate), has a 2D nanosheets structure with large pore size, high surface area and exhibits electrocatalytic activity for OER and HER with extremely low overpotentials. Abstract : Metal–organic framework (MOF) is a powerful material for electrocatalytic applications due to its structural diversity and tunability. Herein, the MOF with an extended organic linker, NiFe(dobpdc), is synthesized and investigated for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). NiFe(dobpdc) features a yarn-ball like structure assembly from 2D nanosheets subunits and high electrocatalytic activity properties. Theoretical calculations suggest the dobpdc 4− can extract/release charges in the electrocatalytic reaction of (* → OH*) and (OH* → O*), respectively. This bifunctional NiFe(dobpdc) electrocatalyst significantly elevates electrocatalytic performance with a lowest overpotential of 207 mV@10 mA cm −2 for OER and 113 mV@10 mA cm −2 for HER, meanwhile, the ultralow overpotentials needed to achieve the high current density of 100 mA cm −2 for OER (251 mV) and HER (170 mV). This study provides a promising strategy to design MOF electrocatalysts for electrocatalytic applications.